The subjectivity of best practices in flood protection - Twaróg, Bernard (Gospodarka w Praktyce i Teorii, 2015)
Despite the continual process of and progress in flood control activities, nevertheless humans andtheir technology have a limited influence on flood events, and as a consequence the results aredramatically inadequate compared to expenses incurred. In addition, wrong decisions and/or anunsuitable solution may lead to undesirable damage. The analyses contained below emphasis therole of preventive actions based on a comprehensive consideration of the various economic, socialand environmental factors. This paper also emphasizes a fact that is confirmed during each flood: thecontinual development of flood prevention infrastructure (e.g. embankments) paradoxically resultsin a limitation of flood control and escalates potential hazards. This paper proposes a revision of thecriteria applied in seeking the best flood control method, by considering the risk and taking into accountexternal cost components and the hazard potential.